Nanoassemblies formed from amphiphilic pillar[5]arene–rod–coil macromolecules in water for the detection of aliphatic diamines. (March 2022) - Lu, Jie; Gou, Xiaoliang; Deng, Yingying; Pei, Yi-Rong; Huang, Zhegang; Jin, Long Yi
Abstract: An amphiphilic pillar[5]arene–rod–coil macromolecule (H 1 ) composed of pillar[5]arene, biphenyl, and oligo(ethylene oxide) groups, was synthesized, and its applicability as a soft material for detecting aliphatic diamines was verified. Amphiphile H 1 self-assembled into unique nanorings and shows an obvious lower critical solution temperature effect in aqueous solution. Interestingly, nanoaggregates of H 1 exhibit certain aggregate-induced emission properties owing to the presence of ten electron-rich biphenyl units on the upper and lower sides of the pillar[5]arene block. In addition, various nanoassemblies were precisely constructed from H 1, through the addition of small molecules with electron-acceptor units. This implies that charge-transfer interactions and hydrophilic/hydrophobic effects cooperatively influence the morphology of H 1 to form diverse nanoassemblies in water. Moreover, macromolecule H 1 with the pillar[5]arene block has a good ability to form host–guest complexes with aliphatic diamines in water, with high selectivity; this significantly affects the process of supramolecular nanoassembly. Graphical abstract: Image 1 Highlights: The pillar[5]arene-rod-coil amphiphiles self-assemble into unique nanorings. The aggregates with various morphologies were formed by charge transfer interaction. Some strong electron-acceptor compounds were detected by charge transfer interaction. Some alkyl amines were detected by pillar[5]arene-rod-coil amphiphiles in water.